An Early Childhood Care and Development Policy of Bhutan (Proceedings of the International Conference on Future of Education, 2019)
An early childhood care and education development as the main foundation for any education system is given priority in Bhutan too. This is significant from the drafting of Bhutan’s ECCD policy in 2008.It covers objectives, strategies and mode of implementations befitting Bhutanese children. Now, due to increasing change in the society such an increasing rate of nuclear family households, unemployment, rapid urbanizations. and growing need of the children and in preparing the children for the 21st century, An early childhood and development has been receiving more attention than before in Bhutan. With the change, a visible gap in policy text and implementation has been also noticed by the people in the fields. This change is viewed as an influence from the global networks and the result of globalization, thus, globalization is considered as an influential factor in policy frameworks of under developing countries. The notable difference in care and early learning in between the urban independent ECCD centers and rural ECCD centers has led to study policy interactions at different levels. For this study, policy trajectory method has been chosen to analyze ECCD policy text production, influence and impact of global to local policies.
Keywords: An early childhood care and development policy, globalization, trajectory method, equity and equality.